109 Correlation of HPV genotyping, p16 and HPV immunohistochemistry with clinicopathological features in vulval squamous cell carcinomas. (13th November 2020) - Basha Mohamed, M; Arora, R
Abstract : Introduction: Human papilloma virus (HPV) associated vulval squamous cell carcinoma (VSCC) has better prognosis than HPV-independent VSCC. Ancillary tests are necessary as morphology alone is unreliable in differentiating these. Methods: We analysed 18 VSCC cases by comparing their morphology with three ancillary tests performed to identify the HPV status. Results: Basaloid/warty type VSCC considered to be HPV-associated; accounted for 6/18 cases (33.3%). Of these, 5 cases (83.3%) showed block p16 positivity and 3 cases (50%) had a positive HPV genotyping result. Keratinising VSCC considered to be HPV-independent; accounted for 11/18 cases (61.1%). Amongst these, 3 cases (27.3%) showed block 16 positivity and 2 cases (18.2%) had positive HPV genotyping results. In one case, the VSCC was too small to assess the morphology. Usual type VIN considered to be HPV-associated, was seen in 11/18 cases (61.1%). Of these, 8 cases (72.7%) showed block p16 positivity and 6 cases (54.5%) had a positive HPV genotyping result. Differentiated VIN considered to be HPV-independent, was seen in 4/18 cases (22.2%). Amongst these, 0 cases (0%) showed block p16 positivity and 0 cases (0%) had a positive HPV genotyping result. HPV genotyping detected high risk HPV in 6/18 cases (33.3%) and all these cases showed block p16 positivity. In 3/9 cases (33.3%), with block p16 positivity, genotyping did not reveal any HPV. HPV immunohistochemistry was negative in all cases. Conclusion: Our study illustrates that in the absence of a gold standard test for HPV, p16 immunohistochemistry and HPV genotyping are complimentary ancillary tests in VSCC.